(untitled) (Sociologisk Forskning, 1998)
TV-journalism of attraction The contemporary media society is characterized by an overabundance of information, messages and images, but a shortage of attention. The competition for the attention of potential audiences, and the problem of audience appeal, has become an increasingly important aspect of journalism and media production. Journalism that does not succeed in this competition is a dead journalism. This article presents a conceptual framework for studies of TV journalism as communication, including different intentions, strategies applied to appeal to viewers, processes of production, bases for audience involvement, roles and relations. I differentiate three modes of communication: information, story-telling and attractions. The article devotes most attention to the concept of attraction as it is the most theoretically innovative of the three. The concept TV journalism of attraction is introduced and elaborated as an important concept in media and journalism studies.